A STRATEGIC CONTROL MODEL FOR THE SANITATION SECTOR IN PERU - Humanchumo Venegas, Henry (2006)
This article deals about the strategic control model and the analysis of the standardized indicators for a sample of sanitation companies in Peru. It is a very important proposal for these organizations that are in an economic and financial chaos.